2016
DOI: 10.1080/2326263x.2016.1193458
|View full text |Cite
|
Sign up to set email alerts
|

Do the stimuli of an SSVEP-based BCI really have to be the same as the stimuli used for training it?

Abstract: International audienceDoes the stimulation used during the training on an SSVEP-based BCI have to be similar to that of the end use? We recorded six-channel EEG data from 12 subjects in various conditions of distance between targets, and of difference in color between targets. Our analysis revealed that the stimulation configuration used for training which leads to the best classification accuracy is not always the one which is closest to the end use configuration. We found that the distance between targets du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…In order to combine several two-class LDA classifier to classify between more classes, the chosen class is the one maximizing d i . Previous studies Évain et al ( 2016 ) have found that such a classifier shows a precision of the order of 65% for each 0.5 s time window. A better accuracy can be reached by adding a voting step.…”
Section: Combining Gaze and Bci Inputs For Target Selectionmentioning
confidence: 87%
See 1 more Smart Citation
“…In order to combine several two-class LDA classifier to classify between more classes, the chosen class is the one maximizing d i . Previous studies Évain et al ( 2016 ) have found that such a classifier shows a precision of the order of 65% for each 0.5 s time window. A better accuracy can be reached by adding a voting step.…”
Section: Combining Gaze and Bci Inputs For Target Selectionmentioning
confidence: 87%
“…The resulting optimal parameters found in this pre-experiment (see Table 2 ) were used for the main experiment. Overall, the sequential method is prone to generate false positives, because of the limited precision of the BCI, the raw accuracy of the BCI classifier p is estimated at 65%, based on previous studies with similar design and signal processing (Évain et al, 2016 ). Thus, in order to optimize the sensitivity, the chosen parameters were quite conservative, with a high threshold of activation.…”
Section: Experimental Evaluationmentioning
confidence: 99%
“…Qualitative properties: Shape, spherical or rectangular/sharp, symmetrical or not, convex or concave, etc; Size, big/small, or fitting in one's hand, etc; Material, it can be rugged or smooth, organic or plastic, etc; Color, the difference in colours of targets in SSVEP [74] influenced performance. The largest SSVEP response was produced by red light at 11Hz [91].…”
Section: Object Propertiesmentioning
confidence: 99%
“…Moreover, word auto-completions were developed for faster P300 spelling [75]. For SSVEP, 'using distant targets of different colours seems to lead to the best and more robust performance in all end use contexts' [76]. In addition, SSVEP does not require a high visual attention or cognitive workload [17].…”
Section: Related Work On Bci User Trainingmentioning
confidence: 99%
See 1 more Smart Citation